2002
DOI: 10.1002/dmrr.283
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of diabetic nephropathy in mice by a diet low in glycoxidation products

Abstract: Intake of high-level, food-derived AGEs is a major contributor to DN in T1D and T2D mice. Avoidance of dietary AGEs provides sustained protection against DN in mice; providing the rationale for similar studies in human diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
151
1
8

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(171 citation statements)
references
References 49 publications
11
151
1
8
Order By: Relevance
“…Positive correlation between dAGE content and serum/tissue AGE levels have been also confirmed by several animal study [17,27,28]. For example Peppa et al [29] to assess the role of dAGEs on type 1 diabetes, exposed the genetically susceptible NOD mice to a high-AGE diet and to a nutritionally similar diet with approximate fivefold-lower levels of CML and MG and demonstrated that after 44 weeks of treatment, NOD mice fed with Low-AGE diet showed almost half of serum AGE levels respect to High-AGE diet fed NOD mice.…”
Section: Dages Intestinal Absorptionsupporting
confidence: 55%
“…Positive correlation between dAGE content and serum/tissue AGE levels have been also confirmed by several animal study [17,27,28]. For example Peppa et al [29] to assess the role of dAGEs on type 1 diabetes, exposed the genetically susceptible NOD mice to a high-AGE diet and to a nutritionally similar diet with approximate fivefold-lower levels of CML and MG and demonstrated that after 44 weeks of treatment, NOD mice fed with Low-AGE diet showed almost half of serum AGE levels respect to High-AGE diet fed NOD mice.…”
Section: Dages Intestinal Absorptionsupporting
confidence: 55%
“…The structural and functional LDL changes found in the present studies were consistent with the differences in AGE content of the diet, with AGE levels in serum as reflected in CML and MG derivatives, but also with levels of the circulating inflammatory markers C-reactive protein, tumor necrosis factor-␣, and VCAM-1 reported previously. 18 These findings supported the postulated relationship between exogenous AGE and diabetic cardiovascular disease 18,28,29 and opened a new window into the mechanisms involved in these events.…”
Section: Discussionmentioning
confidence: 54%
“…Human studies confirmed that about 10% of exogenous AGEs are absorbed and correlate with circulating and tissue AGEs levels, exceeding their endogenous production [11]. Data in humans and experimental animals favor that exogenous food-ingested AGEs result in elevated serum levels and increased tissue deposition [12,13]. Specifically, ingestion of a meal rich in AGEs has led to increased serum levels of AGEs in diabetic patients, which were compared with controls, and tissue deposition was enhanced when the AGE meals were rich in fat [11].…”
Section: Introductionmentioning
confidence: 92%